Multicentre European study of thalamic stimulation in essential tremor: a six year follow up. Issue 10 (20th October 2003) - Sydow, O; Thobois, S; Alesch, F; Speelman, J D
Abstract : Background: Thalamic stimulation is an efficient treatment for disabling essential tremor, as previously shown, but follow up has mostly been short term. Objectives: To see whether good results can be maintained in the longer term. Methods: 37 patients with essential tremor had implantation of a thalamic stimulator, either unilaterally or bilaterally. The results at one year have been reported earlier. After six years, 19 patients were available for follow up. The main instrument for evaluation was the essential tremor rating scale. The patients were examined with pulse generators turned on and off. Results: In the majority of patients, the very good results with stimulation seen at one year were maintained after a mean of 6.5 years. The reduction in tremor scores and improvement in activities of daily living were highly significant compared with baseline and with the stimulation turned off. There were few serious adverse events. Minor side effects related to stimulation were common. Few device related complications were observed and most could be resolved. Conclusions: Good reduction in tremor can be maintained for more than six years in the majority of these severely disabled patients. Thalamic stimulation can be recommended in essential tremor where there is insufficient response to drug treatment. Surgical procedures and follow up should be concentrated in relatively few centres, which will thereby acquire a high degree of expertise.